Pyrolysis Characteristics of Cellulose Isolated from Selected Biomass Feedstocks using a Thermogravimetric Analyser. (December 2017) - Zhang, Zhezi; Zhu, Mingming; Zhang, Dongke
Abstract: Utilisation of biomass by means of pyrolysis has received great interests for the production and use of biofuels. Biomass consists of three major components, namely, cellulose, hemicellulose and lignin and their contents vary from feedstock to feedstock. Understanding the pyrolysis behavior of each component and their interactions holds a key to understanding the complex biomass pyrolysis process. This study was aimed to compare the pyrolysis characteristics of cellulose from various biomass resources. Cellulose samples isolated from selected raw biomass materials, namely, pine wood and wheat straw, in addition to a pure cellulose sample acquired from Sigma Aldrich as a reference, were used in this study. The raw biomass sample was first milled to a particle size fraction of < 310 μm and treated using Soxhlet extraction in a 2:1 (v/v) toluene/ethanol solvent to remove wax. Lignin was then removed by treating the de-waxed sample in a 1M NaClO2 solution at 343K until the product became white. Finally, hemicellulose was leached out by soaking the de-lignified sample in a 6 wt % KOH solution at room temperature overnight and then at the same concentration at 353K for 2 h. Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometer (XRD) were applied to characterise the surface functional groups and the crystallinity of the cellulose samples. The pyrolysis experiments were performed using a thermogravimetric analyser (TGA) in nitrogen at 10Kmin -1 heating rate from room temperature to the final temperature of 823K. The FTIR and XRD results indicated that cellulose can be successfully isolated from the raw biomass samples via the chemical treatment used. The cellulose isolated from both pine wood and wheat straw showed similar pyrolysis characteristics but differed significantly from the reference cellulose. The DTG curves of cellulose samples isolated showed characteristic peaks at 600 and 608K, ca 5-13K lower than that of the reference cellulose and exhibited a large flat shoulder in the temperature range of 475 – 575K. It was identified that the cellulose samples isolated from selected biomass had lower crystallinity and smaller crystallite compared to the reference cellulose, which in turn, impacted on their pyrolysis behavior.